Isothermal oxidation of Inconel 625 superalloy at 800 and 1000 °C: Microstructure and oxide layer characterization - de Sousa Malafaia, Artur Mariano; de Oliveira, Rafaela Brino [UNESP]; Latu-Romain, Laurence; Wouters, Yves; Baldan, Renato [UNESP] (Elsevier, 2020)
Superalloys are widely used in applications at high temperatures and severe environments. Inconel 625 is one of the most applied superalloys due to its high oxidation resistance and mechanical properties, however studies in air lab and temperatures not so extreme as 800 °C are still incipient, mainly regarding microstructure characterization and phases formed during aging at high temperatures. The aim of this study was investigating the Inconel 625 isothermal oxidation behavior at 800 and 1000 °C for 120 and 240 h in air lab. Thermodynamic simulation was used to guide microstructural characterization performed by SEM/EDS and XRD techniques. As-received microstructure presented titanium-niobium (carbo)nitrides and precipitates at grain boundaries. After oxidation, the oxide layer was identified as predominantly chromia in all conditions, providing high oxidation resistance, with some manganese oxidation, suggesting spinel MnCr2O4 formation at 1000 °C, besides ABO4 oxide. Internal alumina oxidation was also observed. Delta phase (Nb,Mo)Ni3 was noticed at grain boundaries (800 °C) and at metal/oxide interface for both temperatures as result of chromium depletion. Some spallation zones were observed at 1000 °C, but this fact did not decrease the good oxidation resistance, as observed at 800 °C. Finally, photoelectrochemistry (PEC) result demonstrated a p-type semiconductor character for chromia scale after 120 h at 800 °C, that was associated to the porous oxide layer and delta phase formation.
Keywords: Chromia scale; Inconel 625; Isothermal oxidation; Microstructure characterization; Thermodynamic simulation; δ-Phase